An integrated radar-communication system using OFDM and DSSS techniques - Liu, Tianchan (Nanyang Technological University, 2022)
The integrated Radar-Communication has an extensive use in civil and military applications, including target detection using radar signals, and secret communication using communication signals. As the development of technology, the architectures and hardware of the radar and communication systems are more and more similar. In order to save space and reduce the interference between systems, the radar and communication systems can be integrated together. As the band used for the two signals are more and more closed. The dissertation aims to design an integrated signal to achieve the functions of target detection and secret communication. The integrated radar-communication system for signal sharing uses direct sequence spread spectrum technique on the basis of the orthogonal frequency division multiplexing architecture. Analyzing the radar and communication performance, an integrated system with strong resistance to the multi-path effect and good bit rate performance is shown in Matlab result.